PENGAMATAN PERTUMBUH MISELIUM JAMUR TIRAM PUTIH (Pleurotus ostreatus (Jacq). P.kummer) PADA MEDIA DASAR SERBUK GERGAJI DENGAN SUPLEMENTASI AMPAS SAGU - Wahyu Hidayat; Umrah Umrah; Meryany Ananda (Biocelebes, 2019)
The study of observation of growth media formulation of white oyster mushrooms’s mycelium (Pleurotus ostreatus (Jacq.) P.Kummer) on the base with sago pulp supplementation medium was conducted from March to May 2018 at Biotechnology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences, Tadulako University. This study were aimed to determine the appropriate formulation and dosage as supplementation of sago pulp with basic media for the growth of the white oyster mushroom mycelium. This study was conducted by Randomized Complete Random Design (RAL), consisted of seven treatments and four replications with basic media and supplementary M0 (100%: without supplements), M1 (95% : 5%), M2 (90% : 10%), M3 (85% : 15%), M4 (80% : 20%), M5 (75% : 25%), M6 (70% : 30%). The results showed that the best growth of mycelium on treatment M0 and M1, mycelium filled the media for 26 days with the average growth of mycelium M0 and M1 were 0,56 cm/ day. The best formulation and dosage of sago suplementation on the base medium were found in M1 (95% base medium: 5% sago pulp).